Analisis Putusan Pengadilan Negeri Blitar Nomor 322/Pid.B/2019/PN.Blt Perspektif PERMA Nomor 2 Tahun 2012 - Henokh Richardo Saroha Jaya Panjaitan (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to conduct an in-depth analysis of the Blitar District Court Decision Number 322/Pid.B/2019/PN.Blt. The analysis is then related to Supreme Court Regulation Number 2 of 2012 concerning the Adjustment of Minor Criminal Offenses and the Amount of Fines in the Criminal Code. This study also discusses the trial process related to theft offenses. The analysis method used in this study is the normative-empirical method. Data collection techniques were conducted through literature study and interviews. The literature study involved reading laws and court decisions. In-depth interviews were conducted with a Class 1A Judge at the Blitar District Court. The research results conducted at the Blitar District Court show that the trial process up to the verdict does not comply with Supreme Court Regulation Number 2 of 2012 concerning the Adjustment of Limits for Minor Crimes and the Amount of Fines in the Criminal Code.